PENGUATAN KAPASITAS PENGELOLAAN KEUANGAN DI UPTD PPA KABUPATEN ACEH UTARA SEBAGAI STRATEGI PEMBERDAYAAN PEREMPUAN - Anis Farhana; Mutia Rahmi; Nasya Nabila; Zuhra Ulvina; Teuku Zulkarnain (Jurnal Sosial Humaniora Sigli, 2025)
Transparent, accountable, and effective financial management is a key factor in supporting the success of women’s empowerment programs at the regional level. Transparency and accountability in financial governance function not only as administrative control instruments, but also as a manifestation of public institutions’ responsibility to the community and stakeholders. In this context, the Technical Implementation Unit for Women’s and Children’s Protection (UPTD PPA) of Aceh Utara Regency holds a strategic role as an implementing agency under the Department of Social Affairs, Women’s Empowerment, and Child Protection, tasked with providing protection services, assistance, and empowerment for women and children experiencing violence or other social issues. This research aims to analyze the current condition of financial management at UPTD PPA Aceh Utara, identify various challenges and obstacles encountered in its implementation, and formulate institutional capacity-strengthening strategies that can improve the effectiveness, efficiency, and accountability of financial management in supporting women’s empowerment programs. The study employs a descriptive qualitative approach, with data collected through in-depth interviews, direct observation, and document review of planning and financial reporting documents. The findings indicate that, in general, UPTD PPA Aceh Utara has implemented financial management in accordance with existing regulations and administrative guidelines, including planning, administration, and financial reporting mechanisms that follow the regional financial system. However, the research also identifies several issues affecting the effectiveness and accountability of financial management, including limited human resource (HR) capacity in the financial sector, weak internal monitoring and evaluation systems, and suboptimal transparency of financial information to the public and relevant stakeholders. Additionally, the study finds that budget constraints and high workloads have hindered the optimal implementation of women’s empowerment activities. Another influencing factor is the limited training and technical assistance provided to UPTD staff regarding performance-based and gender-responsive financial management. Therefore, strengthening institutional capacity is necessary through enhancing HR competencies, developing digital-based financial reporting systems, and applying more participatory, transparent, and results-oriented financial governance principles.The results of this study are expected to provide both practical and academic contributions for local governments in formulating policies to improve the financial governance of UPTD PPA, thereby strengthening the institution’s role in supporting sustainable, inclusive, and gender-equitable women’s empowerment programs. Pengelolaan keuangan yang transparan, akuntabel, dan efektif merupakan salah satu faktor kunci dalam mendukung keberhasilan program pemberdayaan perempuan di tingkat daerah. Transparansi dan akuntabilitas dalam pengelolaan keuangan tidak hanya berfungsi sebagai instrumen pengendalian administrasi, tetapi juga sebagai wujud tanggung jawab lembaga publik terhadap masyarakat dan pemangku kepentingan. Dalam konteks tersebut, UPTD Perlindungan Perempuan dan Anak (PPA) Kabupaten Aceh Utara memiliki peran strategis sebagai lembaga pelaksana teknis di bawah Dinas Sosial, Pemberdayaan Perempuan dan Perlindungan Anak yang bertugas memberikan layanan perlindungan, pendampingan, serta pemberdayaan bagi perempuan dan anak yang mengalami kekerasan atau permasalahan sosial lainnya. Penelitian ini bertujuan untuk menganalisis kondisi aktual pengelolaan keuangan di UPTD PPA Kabupaten Aceh Utara, mengidentifikasi berbagai tantangan dan kendala yang dihadapi dalam pelaksanaannya, serta merumuskan strategi penguatan kapasitas kelembagaan yang dapat meningkatkan efektivitas, efisiensi, dan akuntabilitas pengelolaan keuangan dalam mendukung program pemberdayaan perempuan. Pendekatan yang digunakan adalah pendekatan kualitatif deskriptif, dengan teknik pengumpulan data melalui wawancara mendalam, observasi langsung, dan studi dokumentasi terhadap berbagai dokumen perencanaan dan pelaporan keuangan. Hasil penelitian menunjukkan bahwa secara umum UPTD PPA Kabupaten Aceh Utara telah melaksanakan pengelolaan keuangan sesuai dengan ketentuan regulasi dan pedoman administrasi yang berlaku, termasuk mekanisme perencanaan, penatausahaan, dan pelaporan keuangan yang mengikuti sistem keuangan daerah. Namun demikian, penelitian ini juga menemukan sejumlah permasalahan yang memengaruhi efektivitas dan akuntabilitas pengelolaan keuangan, di antaranya keterbatasan kapasitas sumber daya manusia (SDM) di bidang keuangan, lemahnya sistem monitoring dan evaluasi internal, serta belum optimalnya keterbukaan informasi keuangan kepada publik dan pihak-pihak terkait. Selain itu, penelitian menemukan bahwa keterbatasan anggaran dan beban kerja yang tinggi menyebabkan pelaksanaan kegiatan pemberdayaan perempuan belum sepenuhnya berjalan optimal. Faktor lain yang turut memengaruhi adalah minimnya pelatihan dan pendampingan teknis bagi aparatur UPTD terkait pengelolaan keuangan berbasis kinerja dan responsif gender. Oleh karena itu, diperlukan strategi penguatan kapasitas kelembagaan melalui peningkatan kompetensi SDM, pengembangan sistem pelaporan keuangan berbasis digital, serta penerapan prinsip tata kelola keuangan yang lebih partisipatif, transparan, dan berorientasi pada hasil. Hasil penelitian ini diharapkan dapat memberikan kontribusi praktis dan akademis bagi pemerintah daerah dalam merumuskan kebijakan peningkatan tata kelola keuangan UPTD PPA, sehingga dapat memperkuat peran lembaga ini dalam mendukung pelaksanaan program pemberdayaan perempuan yang berkelanjutan, inklusif, dan berkeadilan gender.